2021
DOI: 10.3390/cancers13153651
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Models of Hepatocellular Carcinoma—A Preclinical Perspective

Abstract: Hepatocellular carcinoma (HCC), the most frequent form of primary liver carcinoma, is a heterogenous and complex tumor type with increased incidence, poor prognosis, and high mortality. The actual therapeutic arsenal is narrow and poorly effective, rendering this disease a global health concern. Although considerable progress has been made in terms of understanding the pathogenesis, molecular mechanisms, genetics, and therapeutical approaches, several facets of human HCC remain undiscovered. A valuable and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 184 publications
0
44
0
Order By: Relevance
“…Thereafter, the cells employed for this study were cultured at low passages to avoid any lack of reliability. HepaRG is an immortalized human hepatic progenitor cell line recently emerging as a useful in vitro model for toxicological evaluations, representing one of the most employed cell lines for the study of drug-induced toxicity [28][29][30]. Compared to primary hepatocytes, HepaRG cells are more advantageous in terms of availability and reproducibility [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the cells employed for this study were cultured at low passages to avoid any lack of reliability. HepaRG is an immortalized human hepatic progenitor cell line recently emerging as a useful in vitro model for toxicological evaluations, representing one of the most employed cell lines for the study of drug-induced toxicity [28][29][30]. Compared to primary hepatocytes, HepaRG cells are more advantageous in terms of availability and reproducibility [28].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several mouse models for the study of hepatocarcinogenesis exist; however, available rodent models can be very diverse in terms of tumor development and histological subtypes heavily depending on their strain and biological background [ 28 , 42 ]. Often genetically engineered mice develop cancer without premalignant lesions or early tumors are not detected in the endpoint studies [ 28 , 43 ]. GEMM or chemically induced mouse models are widely used to study specific genes of interest or drug interactions but only few authors specifically address the role of the tumor vasculature [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Signs of chronic damage, like severe cell infiltration and necrosis of the centrilobular tissue, were discovered in the 4 th week (Fig 12b). 44 Lobular collapse and severe fibrosis were discovered in the 8 th week (Fig 12c)…”
Section: And Fig 5 -Fig 10)mentioning
confidence: 98%
“…In the 2 nd week (Table 2), histopathological studies showed non-specific damages like cellular infiltration and cellular swelling. [43][44] Cellular infiltration was primarily discovered in 2 nd week (Fig 12a). Signs of chronic damage, like severe cell infiltration and necrosis of the centrilobular tissue, were discovered in the 4 th week (Fig 12b).…”
Section: And Fig 5 -Fig 10)mentioning
confidence: 99%
See 1 more Smart Citation